Teledentistry and one health: a sustainable framework for oral and planetary health - Naresh, Arish; Morse, Zac; Bettiol, Silvana (Frontiers in Dental Medicine, 2025)
This community case study documents the integration of One Health approaches in a teledentistry initiative designed to enhance oral health access for children in Tairāwhiti, New Zealand, a region where Māori children experience significantly higher rates of dental decay than non-Māori. Health New Zealand Tairāwhiti established a virtual dental clinic for children aged 0–2 years, providing care through mobile phones and Zoom. The initiative incorporated the Māori concept of “whakawhanauatanga” to build rapport while conducting assessments and delivering preventive guidance. Between March and December 2024, the service delivered 656 appointments, including 114 for patients in rural locations, resulting in a substantial reduction in travel time and associated carbon emissions. The program utilized a family-based enrollment approach that facilitated access for siblings who might otherwise have remained outside the oral health system into care. This model addresses multiple dimensions of planetary health and the One Health framework simultaneously improving clinical access for vulnerable populations, enhancing preventive education, supporting culturally responsive care for Māori families, and reducing environmental impacts through decreased travel. The findings demonstrate how teledentistry, when designed with sustainability principles, can effectively address oral health inequities while contributing to planetary health through reduced carbon footprint.